2006
DOI: 10.1089/ten.2006.12.751
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte and Kupffer Cells Co-cultured on Micropatterned Surfaces to Optimize Hepatocyte Function

Abstract: One strategy for temporarily extending the lives of patients with liver failure is the use of bioartificial liver (BAL) support devices. The functional components of BALs are the parenchymal liver cells known as hepatocytes. One design option for further improving current BAL performance levels is to include the non-parenchymal cells of the liver (e.g., Kupffer cells) in the design. In the current study, the effect of Kupffer cells on hepatocyte function was investigated using micropatterned co-cultures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 23 publications
0
59
0
1
Order By: Relevance
“…The type of micropattern used can strongly affect the culture fate [72,77], because it will determine diffusion rates and level of separation or contact between cell populations. Owing to cell polarization, exact positioning may be needed for mammalian cell studies to ensure that population contact is made via the correct cell surface [88].…”
Section: Degree Of Contact Between Populationsmentioning
confidence: 99%
“…The type of micropattern used can strongly affect the culture fate [72,77], because it will determine diffusion rates and level of separation or contact between cell populations. Owing to cell polarization, exact positioning may be needed for mammalian cell studies to ensure that population contact is made via the correct cell surface [88].…”
Section: Degree Of Contact Between Populationsmentioning
confidence: 99%
“…The importance of nonparenchymal cells to mount a response to a lipopolysaccharide (LPS) challenge was demonstrated when these cells were removed from the PHH culture by an additional purification step (Percoll purification) (15). It was recently shown that direct contact between hepatocytes and Kupffer cells affects cell function and viability of both types of cells (16).…”
Section: Hepatocyte Preparation and Culturementioning
confidence: 99%
“…1 Hepatocytes cultured in monolayers (HMs) lose their phenotypic functions and suffer from mRNA degradation within 24 h of their removal from the liver. [2][3][4] Monolayers of liver sinusoidal endothelial cells (LSECs) 5 and Kupffer cells (KCs) 6 also rapidly dedifferentiate within a few days in vitro. Although hepatocytes cultured in a collagen sandwich (CS) or two-dimensional (2D) cocultures have been shown to exhibit stable expression of hepatic markers, 3,7-9 they do not emulate hepatic architecture in vivo.…”
mentioning
confidence: 99%